2008
DOI: 10.1523/jneurosci.3621-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Blocker of N- and T-type Voltage-Gated Calcium Channels Attenuates Ethanol-Induced Intoxication, Place Preference, Self-Administration, and Reinstatement

Abstract: There is a clear need for new therapeutics to treat alcoholism. Here, we test our hypothesis that selective inhibitors of neuronal calcium channels will reduce ethanol consumption and intoxication, based on our previous studies using knock-out mice and cell culture systems. We demonstrate that pretreatment with the novel mixed N-type and T-type calcium channel antagonist 1-(6,6-bis(4-fluorophenyl)hexyl)-4-(3,4,5-trimethoxybenzyl)piperazine (NP078585) reduced ethanol intoxication. NP078585 also attenuated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 55 publications
2
22
0
Order By: Relevance
“…The results of these studies showed that NP078585 reduced the acute effects of ethanol and abolished the expression of ethanol conditioned place preference in mice [334] supporting the hypothesis that N-type calcium channels contribute to ethanol intoxication, reinforcement, reward, and reinstatement.…”
Section: Voltage-gated Calcium Channelssupporting
confidence: 62%
“…The results of these studies showed that NP078585 reduced the acute effects of ethanol and abolished the expression of ethanol conditioned place preference in mice [334] supporting the hypothesis that N-type calcium channels contribute to ethanol intoxication, reinforcement, reward, and reinstatement.…”
Section: Voltage-gated Calcium Channelssupporting
confidence: 62%
“…Furthermore, several lead compounds in 842 this class have been validated in animal models of pain. For the derivatives with a mixed action on Ca V 2.2 and Ca V 3 channels, the addictive and intoxicating narcotic properties of ethanol were also abrogated (Newton et al, 2008). Other derivatives in this class include pyrazolpiperidines (Subasinghe et al, 2012) and aminopiperidine sulfonamide (Shao et al, 2012), both of which have analgesic properties by virtue of N-type channel blocking action.…”
Section: Ca V 2 Channel Pathophysiologymentioning
confidence: 99%
“…Such blockers might also help treat addiction, since rodent studies have shown that NVDCCs promote alcohol intake (Newton et al, 2004) and that NDVCC blockers are antinociceptive, potentiate morphine analgesia, and attenuate morphine tolerance and physical dependence and withdrawal (Meng et al, 2008). Also, NP078585, a blocker of NVDCCs and TVDCCs in human trials for chronic pain, reduces the intoxicating and reinforcing effects of ethanol and abolishes stressinduced reinstatement for alcohol in rats (Newton et al, 2008). These effects on alcohol behaviors were not observed in NVDCC knockout mice, suggesting action through NVDCCs.…”
Section: Other Calcium Channel Antagonistsmentioning
confidence: 99%